2015
DOI: 10.1037/xlm0000060
|View full text |Cite
|
Sign up to set email alerts
|

Invariant spatial context is learned but not retrieved in gaze-contingent tunnel-view search.

Abstract: Our visual brain is remarkable in extracting invariant properties from the noisy environment, guiding selection of where to look and what to identify. However, how the brain achieves this is still poorly understood. Here we explore interactions of local context and global structure in the long-term learning and retrieval of invariant display properties. Participants searched for a target among distractors, without knowing that some "old" configurations were presented repeatedly (randomly inserted among "new" c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 45 publications
12
44
2
Order By: Relevance
“…For example, fixation duration could increase as the total number of fixations decreases, implying that people might become better at planning a sequence of saccades, but not necessarily becoming more efficient in terms of how quickly they search through the display, or process distractor elements, while searching for the target. Zang, Jia, Müller, and Shi (2015) reported exactly this pattern of eye-movement data under gaze-contingent viewing conditions, suggesting that contextual cuing might not necessarily produce faster searches for the target, but could nevertheless improve the efficiency with which searches are conducted, in terms of the number of eye movements made. The observations of Zang et al are somewhat at odds with other studies that reported no influence of cuing on fixation duration (e.g., Tseng & Li, 2004;Zhao et al, 2012).…”
Section: Expedited Searchmentioning
confidence: 59%
See 1 more Smart Citation
“…For example, fixation duration could increase as the total number of fixations decreases, implying that people might become better at planning a sequence of saccades, but not necessarily becoming more efficient in terms of how quickly they search through the display, or process distractor elements, while searching for the target. Zang, Jia, Müller, and Shi (2015) reported exactly this pattern of eye-movement data under gaze-contingent viewing conditions, suggesting that contextual cuing might not necessarily produce faster searches for the target, but could nevertheless improve the efficiency with which searches are conducted, in terms of the number of eye movements made. The observations of Zang et al are somewhat at odds with other studies that reported no influence of cuing on fixation duration (e.g., Tseng & Li, 2004;Zhao et al, 2012).…”
Section: Expedited Searchmentioning
confidence: 59%
“…It is possible that the abbreviated nonproductive stage of search corresponds to more rapid growth of a familiarity signal for repeated displays. The finding that fixation durations are longer for repeated displays (Zang et al, 2015) is readily accommodated under this view, as it suggests that once a search display has achieved a critical level of familiarity, search can proceed more strategically, now guided by the information present at the point of fixation-consistent with the reduced number of saccades needed to reach the target (e.g., Beesley et al, 2017;Harris & Remington, 2017;Manginelli & Pollmann, 2009;Peterson & Kramer, 2001;Tseng & Li, 2004;Zhao et al, 2012). Increased fixation duration coupled with fewer fixations for repeated displays meshes intuitively with the idea that more strategic processes-such as those commonly associated with criterion setting in simple decision tasks (Ratcliff & Rouder, 1998)-may be recruited during the search itself (e.g., deliberating where to direct the next eye movement).…”
Section: Discussionmentioning
confidence: 98%
“…The formation and reinforcement of this perceptual unit across repetitions might be accompanied by an enhancement of its visual saliency [59]. Such a hypothesis in terms of attentional selection might account for a large body of results reported with the standard task, and in particular the enhancement of the N2pc component in repeated contexts, regardless of its involvement in attentional processes, but also the requirement for a limited amount of peripheral information for the expression of CC [56].…”
Section: Reviewmentioning
confidence: 88%
“…Note, however, that separating the context and target by empty space does not abolish learning, suggesting that chunk formation is more constrained by the perceptual organization of items in the display rather than spatial distance per se [54]. Furthermore, although the global context does not need to be repeated, the local benefit is nevertheless dependant both on its relative position in the display and on the availability of a limited amount of peripheral information [56].…”
Section: Reviewmentioning
confidence: 96%
“…Similar to our previous study (Zang, Jia, Müller, & Shi, 2015), both T-shaped and L-shaped stimuli were composed of two equal-length lines-one with horizontal and one with vertical orientation. For the Tshaped stimulus, the lines contact point was at the tip of the vertical line and, respectively, the center point of the horizontal line.…”
Section: Apparatus and Stimulimentioning
confidence: 94%